Perception and use of the internet by adolescents in Ibadan, Nigeria (2004)
The study focused on the perception and use of the Internet by the adolescents in Ibadan, Nigeria. It investigated the types of information sourced from the Internet, the point of access and the constraints to access. The instruments adopted for the study were questionnaire, interview and observation. The study established that the adolescents see the Internet among others as a vital source of information, a window to the world and a source of entertainment. It also established that the cybercafe is the most prominent access point and that access is constrained, among others, by slow connectivity, high cost and server problem. It concluded by proffering solution to the problems of access.